Prevalence and genotype assessment of HPV in 73,697 females from Beijing, China - Bai, Mingjian; Li, Yunxiang; Ma, Fucun; Gao, Qian; Lv, Zhiyong; Xu, Yueming; Feng, Jing; Fu, Fengxian; Liang, Guowei (Frontiers in Public Health, 2025)
BackgroundThe present study aimed to assess the prevalence and genotype distribution of Human papillomavirus (HPV) in Beijing females.MethodsA total of 73,697 subjects [both Department of Gynecology (n = 35,666) and Physical Examination center (n = 38,031)] were retrieved between June 2014 and December 2023. HPV testing was performed by Tellgenplex® HPV-27 DNA genotyping Test system.ResultsAn overall HPV infection rate of 17.28% (12,736/73,697) over the past decade (2014 to 2023), with a significant decrease in annual incidence (p < 0.001). HPV-52, 16, and 58 were predominant in high-risk types, while HPV-61, 81, and 43 were the most prevalent in low-risk HPV types. Age-specific patterns revealed bimodal infection peaks in individuals under 21 and between 51 ~ 56 years. Furthermore, a significant increase in HPV infection rates was observed with the progression of pathological severity (p < 0.001).ConclusionThis study emphasizes the importance of HPV infection rate from real word and developing vaccines specifically for the Chinese population. In the future, it is necessary to design more suitable vaccines based on Chinese HPV type ranking, especially for HR-HPV (HPV-39, HPV-53, and HPV-56) and LR-HPV (HPV-43, HPV-61, and HPV-81).